Pemberdayaan Berkelanjutan: Strategi Akses Desa Wisata sebagai Tameng dari Aktivitas Pertambangan Emas Ilegal Menggunakan Alat Berat - Muh Gazali; Najmul Hayat (Dimasejati: Jurnal Pengabdian Kepada Masyarakat, 2025)
SUSTAINABLE EMPOWERMENT: VILLAGE TOURISM ACCESS STRATEGY AS A SHIELD FROM ILLEGAL GOLD MINING ACTIVITIES USING HEAVY EQUIPMENT. Sungai Telang Village is endowed with abundant natural resources, characterized by pristine water, picturesque hills, stunning waterfalls, preserved village forests, and a network of tributaries flowing around residential settlements. These natural potentials hold tremendous opportunities for development through optimal management. However, the presence of gold deposits in this region has attracted illegal mining activities using heavy equipment that threatens the sustainability of these natural resources. Although the community has conducted conventional resistance through various rejection actions, these efforts have not been sufficiently effective in permanently stopping mining activities. This research employs a sustainable empowerment approach and Participatory Action Research to facilitate the community in identifying and formulating relevant strategies to permanently cease illegal mining operations. Through this approach, the community is expected to play an active role in protecting and preserving their village's natural resource potential sustainably. Thus, environmental conservation efforts can progress alongside community welfare improvement through sustainable and environmentally friendly village potential development. The results of this research are expected to serve as a community-based natural resource management model that can be adapted by other villages facing similar challenges. This study will contribute to the growing body of literature on community-based environmental conservation and sustainable resource management in developing regions. The findings will provide valuable insights into effective strategies for combating illegal mining while promoting sustainable local development.